Changing Modalities in the Globalization of Islamic Saint Veneration and Mysticism: Sidi Ibrahim al-Dasuqi, Shaykh Muhammad 'Uthman al-Burhani and their Sufi Orders - Frishkopf, Michael (Religious Studies and Theology, 2001)
.